2023
DOI: 10.52214/salt.v22i2.10667
|View full text |Cite
|
Sign up to set email alerts
|

Complex Dynamic System Theory in Second Language Acquisition: Exploring Concepts and Unpacking Constructs

Abstract: In January 2000, Stephen Hawking predicted, “the next century will be the century of complexity” (Sanders, 2003). Indeed, complexity science, or the study of the structure and behavior of complex dynamic systems, has become increasingly popular as researchers aim to understand the complexity that surrounds us – e.g., rainforests, immune systems, the global economy, and language (Sanders, 2003). In fact, at the time that Stephan Hawking made his prediction, complexity science and systems thinking had already pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Cluster 4 as presented by yellow, the topics are focused on the intervention of AR video towards problem-solving skills. The studies within this cluster investigate topics such as intelligence AR tutoring system for mathematics teaching and learning [39]; mobile AR for remedial teaching of compound-cube-surface area [40]; video-based AR instruction to teach mathematics [41]; and learning mathematical modelling with AR mobile math [42]. Those researchers revealed that students showed a substantial improvement in their performance and supports students in bridging between real-world situations and mathematical concepts in problem-solving after receiving AR interventions.…”
Section: Fig 4 Network Visualization Of Co-occurrence Analysis Of Abs...mentioning
confidence: 99%
“…Cluster 4 as presented by yellow, the topics are focused on the intervention of AR video towards problem-solving skills. The studies within this cluster investigate topics such as intelligence AR tutoring system for mathematics teaching and learning [39]; mobile AR for remedial teaching of compound-cube-surface area [40]; video-based AR instruction to teach mathematics [41]; and learning mathematical modelling with AR mobile math [42]. Those researchers revealed that students showed a substantial improvement in their performance and supports students in bridging between real-world situations and mathematical concepts in problem-solving after receiving AR interventions.…”
Section: Fig 4 Network Visualization Of Co-occurrence Analysis Of Abs...mentioning
confidence: 99%